Interferon regulatory factor 9 promotes lung cancer progression via regulation of versican - Brunn, David; Turkowski, Kati; Günther, Stefan; Weigert, Andreas; Muley, Thomas; Kriegsmann, Mark; Winter, Hauke; Dammann, Reinhard; Stathopoulos, Georgios T.; Thomas, Michael; Guenther, Andreas; Grimminger, Friedrich; et al. (Cancers, 2021)
Transcription factors can serve as links between tumor microenvironment signaling and oncogenesis. Interferon regulatory factor 9 (IRF9) is recruited and expressed upon interferon stimulation and is dependent on cofactors that exert in tumor-suppressing or oncogenic functions via the JAK-STAT pathway. IRF9 is frequently overexpressed in human lung cancer and is associated with decreased patient survival; however, the underlying mechanisms remain to be elucidated. Here, we used stably transduced lung adenocarcinoma cell lines (A549 and A427) to overexpress or knockdown IRF9. Overexpression led to increased oncogenic behavior in vitro, including enhanced proliferation and migration, whereas knockdown reduced these effects. These findings were confirmed in vivo using lung tumor xenografts in nude mice, and effects on both tumor growth and tumor mass were observed. Using RNA sequencing, we identified versican (VCAN) as a novel downstream target of IRF9. Indeed, IRF9 and VCAN expression levels were found to be correlated. We showed for the first time that IRF9 binds at a newly identified response element in the promoter region of VCAN to regulate its transcription. Using an siRNA approach, VCAN was found to enable the oncogenic properties (proliferation and migration) of IRF9 transduced cells, perhaps with CDKN1A involvement. The targeted inhibition of IRF9 in lung cancer could therefore be used as a new treatment option without multimodal interference in microenvironment JAK-STAT signaling.